Modeling of metal complexes designed for homogeneous catalysis - Aynalı, Figen Kayar (My University, 2012)
HOMOJEN KATALİZ İÇİN METAL KOMPLEKSLERİN MODELLENMESİ Kataliz reaksiyonları sanayi boyutlarında kimyasal değişimlerin gözlemlendiği proseslerin en minimum enerji kullanılarak yapılabilmesinde en önemli rolü üstlenmektedir. Enerjininin minimuma indirgenmesinde kullanılan en yaygın katalizörler ise metal oksitler olarak rastlanmaktadır. Doğal gazın (metan) kısmi oksidasyonu sonucu elde edilebilecek kolay taşınabilir metanolün C-H bağ aktivasyonu homojen katalizör kullanılarak araştırılmıştır. Dehidrojenasyon ve dehidrasyon reaksiyonları OsO+ metal oksit katalizörü kullanılarak metanın aktivasyonu Gaussian 09 ve ADF programları kullanılarak teorik olarak incelenmiştir. İncelenen reaksiyonun gibbs oluşum enerjisinin değişimi elde edilmiştir. Ek olarak Arrhenius grafikleri tüm sunulan reaksiyonlar için elde edilmiş ve aktivasyon enerji değerleri hesaplanmıştır

MODELING OF METAL COMPLEXES DESIGNED FOR HOMOGENEOUS CATALYSIS Catalysis is the key toward accomplishment of industrially significant chemical transformations with minimum energy investment. Transition-metal oxides are one of the common catalysis in oxidation process used to minimize energy investment. The C-H bond activation to form the easily transported liquid fuel methanol from partial oxidation of natural gas (methane) using homogenous catalysis was investigated. The reaction mechanism of the dehydrogenation and dehydration has been investigated theoretically for the activation of methane by OsO+ using Gaussian 09 software and ADF software. The change of the formation gibbs energy of the reactions under investigation has been obtained. In addition, Arrhenius plots of all the proposed reaction were presented along with the calculated corresponding activation energies.
Keywords: Homojen Kataliz; Kimya Mühendisliği; Metal